Determinants of Government Efficiency - Hauner, David (IMF Working Papers; Working Paper ;, 2008)
We compile the first large cross-country panel dataset of public sector performance and efficiency, encompassing 114 countries on all income levels from 1980 to 2006, with about 1,800 country-year observations for the education sector and about 900 observations for health. We regress these indicators on potential economic, institutional, demographic, and geographic determinants. Our most resounding conclusion is that higher government expenditure relative to GDP tends to be associated with lower efficiency in the respective sector. Moreover, we find that richer countries exhibit better public sector performance and efficiency, and that institutional and demographic factors also play a significant role.